A new member of Cu-8(II) family: Synthesis, structure and magnetic properties of an octanuclear copper complex with N-tert-butyldiethanolamine - Nesterov, Dmytro (2017)
A highly-nuclear copper complex [(Cu8O)-O-II((t)BuDea)(5)(H(t)BuDea)Cl-2][(CuCl2)-Cl-I]2H(2)O (1) has been prepared in a one-pot reaction of copper chloride with N-tert-butyldiethanolamine in methanol in the open air. The structure of the complex was established by single-crystal X-ray analysis. The octanuclear close-packed core of 1 belongs to the {M-8((3)-X)(6)(-X)(7)} molecular structure type. The ESI-MS spectroscopy confirmed the stability of the whole core in methanol solution. From the ESI-MS and magnetic data the divalent oxidation state of all eight coppers in the Cu-8 core was proposed. Electrochemical studies were undertaken to confirm the overall Cu-I/Cu-II composition of the complex. Thermogravimetric behaviour was studied and disclosed that the complex 1 is stable until 150C. The magnetic investigations revealed a dominant antiferromagnetic coupling between copper centres within the octanuclear cation. (C) 2016 Elsevier B.V. All rights reserved.